1993
DOI: 10.1016/0014-5793(93)80408-m
|View full text |Cite
|
Sign up to set email alerts
|

The glycine residue of ATP regulatory module in receptor guanylate cyclases that is essential in natriuretic factor signaling

Abstract: Atrial natriuretic factor (ANF) and C-type natriuretic peptide (CNP)-activated guanylate cyclases are single-chain transmembrane-spanning proteins, containing both ligand binding and catalytic activities. In both proteins, ligand binding to the extracellular receptor domain activates the cytosolic catalytic domain, generating the second messenger cyclic GMP. Obligatory in this activation process is an ATP-dependent step. ATP directly binds to a deBned ATP-regulatory module (ARM) sequence motif in the cyclases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Whether ATP binds directly to NPR-A and NPR-B is controversial. Initial reports suggested that the specific intracellular glycine region called the ARM within the kinase homology domain is required for adenine nucleotide regulation (12,13,19). However, a subsequent report indicated that this region is not involved in the regulation of NPR-A (22).…”
Section: Effect Of Atp On a Dephosphorylation-resistant Npr-a Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether ATP binds directly to NPR-A and NPR-B is controversial. Initial reports suggested that the specific intracellular glycine region called the ARM within the kinase homology domain is required for adenine nucleotide regulation (12,13,19). However, a subsequent report indicated that this region is not involved in the regulation of NPR-A (22).…”
Section: Effect Of Atp On a Dephosphorylation-resistant Npr-a Mutantmentioning
confidence: 99%
“…Similar stimulatory effects of ATP were reported for the intestinal and retinal guanylyl cyclases as well (17,42,44). In the early 1990s, it was reported that adenine nucleotides are absolutely required for natriuretic peptide-dependent activation of NPR-A and NPR-B (10,12). These data then led to a two-step activation model, which was left unchallenged until 2005, when we reported that ATP is not essential for activation of natriuretic peptide receptors in human embryonic kidney 293 cells highly overexpressing NPR-A or NPR-B (3,35).…”
mentioning
confidence: 92%
“…Consistent with this idea, cDNA cloning revealed the presence of a motif within the kinase homology domain of NPR-A that resembles the canonical ATP-binding glycine elbow found in many protein kinases (22,23). Because the mutation of this motif resulted in diminished hormonal responsiveness of NPR-A and NPR-B, it was termed the ATP regulatory module (24,25). Together, these data led to a two-step model in which natriuretic peptidebinding facilitates direct ATP binding to the kinase homology domains of NPR-A and NPR-B, which ultimately causes the formation of two active sites per catalytic dimer (10).…”
mentioning
confidence: 66%
“…The ECD contains six cysteine residues that participate in intramolecular disulfide bridges and seven potential N-linked glycosylation sites (Fig. 1c); this is also the case for rat GC-B (5 Xaa-Xaa-Xaa-Gly 525 ) (34) are identical between murine and rat GC-B (Fig. 1c).…”
Section: Structure Of Npr2mentioning
confidence: 99%